Integrated Technological Approaches to Academic Success: Mobile Learning, Social Media, and AI in Visual Art Education - Abeer S. Almogren; Waleed Mugahed Al-Rahmi; Nisar Ahmed Dahri (IEEE Access)
This study examines the impact of mobile learning, social media engagement, and artificial intelligence on academic performance in higher education, based on a theoretical model that includes ubiquitous access, interactivity, information sharing, collaborative learning, motivation, personalized learning, student support, and automation. Employing quantitative methodology, a total of three hundred eighty-one students participated in a survey at King Saud University, both online and in-person. Structural Equation Modeling (SEM) analysis, provided by the SmartPLS tool, was utilized to examine the relationship between these variables. Study findings show that ubiquitous access and interactivity significantly enhance mobile learning. Whereas information sharing and motivation positively influence social media engagement, collaborative learning does not significantly impact it. However, personalized learning and student support were found to positively affect artificial intelligence technology, with Automation further improving its effectiveness. The study also reveals that mobile learning positively affects both social media engagement and academic performance, and artificial intelligence enhances academic performance through personalized support. However, the interaction between Artificial Intelligence and Mobile Learning does not significantly amplify academic benefits. The study highlights the need for a multi-dimensional approach to integrating mobile learning, AI, and social media in education, promoting personalized and adaptive learning environments. Practically, it encourages educators to adopt these technologies for enhanced academic performance and urges policymakers to invest in infrastructure and training for effective implementation.